Gene expression differs in susceptible and resistant amphibians exposed to Batrachochytrium dendrobatidis. Issue 2 (28th February 2018) - Eskew, Evan A.; Shock, Barbara C.; LaDouceur, Elise E. B.; Keel, Kevin; Miller, Michael R.; Foley, Janet E.; Todd, Brian D.
Abstract : Chytridiomycosis, the disease caused by the fungal pathogen Batrachochytrium dendrobatidis ( Bd ), has devastated global amphibian biodiversity. Nevertheless, some hosts avoid disease after Bd exposure even as others experience near-complete extirpation. It remains unclear whether the amphibian adaptive immune system plays a role in Bd defence. Here, we describe gene expression in two host species—one susceptible to chytridiomycosis and one resistant—following exposure to two Bd isolates that differ in virulence. Susceptible wood frogs ( Rana sylvatica ) had high infection loads and mortality when exposed to the more virulent Bd isolate but lower infection loads and no fatal disease when exposed to the less virulent isolate. Resistant American bullfrogs ( R. catesbeiana ) had high survival across treatments and rapidly cleared Bd infection or avoided infection entirely. We found widespread upregulation of adaptive immune genes and downregulation of important metabolic and cellular maintenance components in wood frogs after Bd exposure, whereas American bullfrogs showed little gene expression change and no evidence of an adaptive immune response. Wood frog responses suggest that adaptive immune defences may be ineffective against virulent Bd isolates that can cause rapid physiological dysfunction. By contrast, American bullfrogs exhibited robust resistance to Bd that is likely attributable, at least in part, to their continued upkeep of metabolic and skin integrity pathways as well as greater antimicrobial peptide expression compared to wood frogs, regardless of exposure. Greater understanding of these defences will ultimately help conservationists manage chytridiomycosis.